CONTRIBUTION TO THE KNOWLEDGE OF THE GENUS PRIAPELLA AND DESCRIPTION OF A NEW SPECIES - ALVAREZ, JAVIER A (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1937)
Descr is given of Aprocta anthicola from Buteo b borealis with brief notes on Contracaecum spiculigerum from Phalacrocorax vigua mexicanus, Physaloptera (P) acuticauda from Circus cyaneus hudsonius and Hamato-spiculum insignis from Speotyto cunicular
REV SOC MEX HIST NAT
Keywords: CONTRIBUTION, KNOWLEDGE, GENUS PRIAPELLA, DESCRIPTION, NEW SPECIES; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)